Conventual documentation of origin of Madrid in the Diocesan File of Merida – Badajoz - Pérez Ortiz, Guadalupe; Vivas Moreno, Agustín (Revista General de Información y Documentación, 2013)
The purpose of this article is the analysis of the conventual documents guarded in the Archivo Diocesano de Mérida-Badajoz, that they reflect in his hackneyed byline the population of Madrid. For it, after the exhibition of a few historical notes of our file, we will realize an analysis of the documentation from multiple perspectives: manuscript or form, chronology, language, entities and contents. After this analysis we will approach the motive for which there exists in this Extremadura file an important area of conventual documents with the above mentioned origin. The study concludes with the documentary catalogue.